microRNA-1271-5p/TIAM1 suppresses the progression of ovarian cancer through inactivating Notch signaling pathway - Feng-Juan Han; Jia Li; Ying Shen; Ying Guo; Yi-Chao Liu; Yang Yu; Jia-Yue Xu; Shao-Xuan Liu; Yan-Hong Wang (BMC, 2020)
Abstract Objective Ovarian cancer (OC) has been regarded as the most malignant gynecological neoplasm and often confers grave outcomes owing to the frequent metastasis and high recurrence. A previous study has demonstrated that miR-1271-5p is implicated in OC progression, however, the possible mechanism of it remains unknown. The purpose of this investigation was to explore how miR-1271-5p regulates the progression of OC. Methods Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases were employed to analyze the differentially expressed miRNAs or genes as well as their corresponding prognostic values. miR-1271-5p expression in OC cells was examined by qRT-PCR. Cell counting kit 8 (CCK-8), colony formation, and transwell tests were conducted to evaluate the proliferation, migration and invasion potentials. Bioinformatics prediction and luciferase activity analysis were utilized to predict and verify the target gene of miR-1271-5p. Western blot assay was carried out to measure protein expression. Results miR-1271-5p was significantly decreased in OC and its down-regulation was associated with the grave outcome of OC patients. Upregulation of miR-1271-5p inhibited cell viability, but miR-1271-5p knockdown promoted the proliferation of OC cells. TIAM1 was a direct target gene of miR-1271-5p and expressed in OC tissues at higher level. High expression of TIAM1 induced the poorer prognosis of patients with OC. Further functional analyses showed that the suppressive role of miR-1271-5p on OC cell malignant behaviors was overturned by the upregulation of TIAM1. The protein levels of Cyclin D1, HES1, NOTCH and NUMB were remarkably changed due to the abnormal expression of miR-1271-5p and TIAM1. Conclusion To sum up, miR-1271-5p inhibits proliferation, invasion and migration of OC cells by directly repressing TIAM1 to inactivate the Notch signaling pathway, which provides an alternative therapeutic candidate for the advancement of OC treatment.